Semen Proteomics Reveals the Impact of Enterococcus faecalis on male Fertility - Grande, Giuseppe; Vincenzoni, Federica; Mancini, Francesca; Baroni, Silvia; Luca, Giovanni; Calafiore, Riccardo; Marana, Riccardo; Castagnola, Massimo; Pontecorvi, Alfredo; Milardi, Domenico (Protein and Peptide Letters, 2018)
Background: Infectious etiologies contribute to 15% of male factor infertility. Enterococcus faecalis (E. faecalis) is commonly identified in semen culture of infertile men and it is associated with significantly poorer semen quality. Objective: Aim of this study was to identify new seminal biomarkers for the male tract infection by E. faecalis, using proteomic profiling, in order to understand the effect of E. faecalis on the physiopathology of male reproduction. Methods: We included in the study ten patients seeking medical care for primary infertility with prostate-vesicular-epidydimitis and with microbiological analysis on semen and/or prostatic secretions positive for E. faecalis. Ten fertile men have been enrolled as a control group in the protocol. An aliquot of each seminal plasma was subjected to an in-solution digestion protocol and analyzed using an Ultimate 3000 RSLCnano HPLC apparatus coupled to a LTQ Orbitrap Elite mass spectrometer. Results: Eight proteins have not been identified in the group of controls and have been observed in a remarkable proportion of patients, mainly involved in immune system activity (CD177, Swiprosin-1 and 2-oxoglutarate dehydrogenase). Arylsulfatase has been identified in the group of controls and was absent in all patients with infection. Three proteins (TIMP-1, WFDC domain protein 2 and Carboxypeptidase E) have been observed significantly different in patients versus controls, mainly related with inflammation. Conclusions: This is the first application of MS-based proteomics aimed to reveal an array of proteins in the seminal plasma and reflecting the effect of the infection by E. faecalis on semen composition.
Keywords: MAGI